KETERLIBATAN ORANG TUA DALAM RUMAH TANGGA ANAK DI KELURAHAN GURAPING KECAMATAN OBA UTARA - Syahjuan, Yusril Ahda; Abubakar, Fatum; Alhadar, Muhdi (Indonesian Journal of Shariah and Justice, 2022)
The purpose of this study was to determine the form of parental involvement in children's households in the Guraping Village, North Oba District, Tidore Islands City. The results of the study describe the habits of parents who do not understand their position in the midst of children's family life so that parents are not the arbiters between their children's disputes as husband and wife, but as unilateral decision- making that harms life between husband and wife in this case their children. The conclusion from this study is that parental involvement in children's households does not always have a positive impact on their children. In Islamic law the involvement of parents in a child's household is permissible as long as it does not contain elements of tyranny, mediating between children's disputes is not based on reasons of economic conflict. Parents must be a source of solutions for both.